Zebrafish endochondral growth zones as they relate to human bone size, shape and disease - Le Pabic, Pierre; Dranow, Daniel B.; Hoyle, Diego J.; Schilling, Thomas F. (Frontiers in Endocrinology, 2022)
Research on the genetic mechanisms underlying human skeletal development and disease have largely relied on studies in mice. However, recently the zebrafish has emerged as a popular model for skeletal research. Despite anatomical differences such as a lack of long bones in their limbs and no hematopoietic bone marrow, both the cell types in cartilage and bone as well as the genetic pathways that regulate their development are remarkably conserved between fish and humans. Here we review recent studies that highlight this conservation, focusing specifically on the cartilaginous growth zones (GZs) of endochondral bones. GZs can be unidirectional such as the growth plates (GPs) of long bones in tetrapod limbs or bidirectional, such as the synchondroses of the mammalian skull base. In addition to endochondral growth, GZs play key roles in cartilage maturation and replacement by bone. Recent studies in fish suggest key roles for cartilage polarity in GZ function, surprisingly early establishment of signaling systems that regulate cartilage during embryonic development, and important roles for cartilage proliferation rather than hypertrophy in bone size. Despite anatomical differences, there are now many zebrafish models for human skeletal disorders including mutations in genes that cause defects in cartilage associated with endochondral GZs. These point to conserved developmental mechanisms, some of which operate both in cranial GZs and limb GPs, as well as others that act earlier or in parallel to known GP regulators. Experimental advantages of zebrafish for genetic screens, high resolution live imaging and drug screens, set the stage for many novel insights into causes and potential therapies for human endochondral bone diseases.